Sosialisasi Terkait Peran Organisasi Pemuda dalam Mendukung Pencapaian SDGs di Indonesia - Pongtambing, Yulita Sirinti; Manapa, Esther Sanda; Appa, Felycitae Ekalaya; Kalalinggi, Septaria Yolan; Sampetoding, Eliyah Acantha Manapa (Institut Nalanda, 2024)
Achieving the Sustainable Development Goals (SDGs) requires joint efforts from various stakeholders, including government institutions, academics, philanthropic organizations, the business world, and civil society groups. By utilizing the unique strengths and resources of each sector, this is an effort to encourage synergy, innovation and inclusiveness in overcoming various sustainable development challenges. The socialization in this service aims to obtain input from young lecturers in identifying the role of youth organizations in encouraging the achievement of Sustainable Development Goals (SDGs) in Indonesia. Through analysis of group discussions by relevant resource persons, this service encourages resource persons to explain the contribution of youth organizations in increasing awareness, participation and community support for the SDGs. The results of the service show that input from resource persons related to youth organizations plays an important role in accelerating the achievement of the SDGs. Recommendations are given to strengthen the role of youth organizations through active participation in sustainable development programs supported by the government. This service provides valuable insight for the management of DPP PARKINDO and PUSARI ID in developing collaborative strategies to achieve SDGs in Indonesia which can be started from their respective organizational circles first.